Application of data mining and complex networks in the representation of purchasing associations: a case study in supermarket purchases - Lima, Maicon; Castro, Melque Henrique; Leite, Thiago; Cordeiro, Douglas; da Silva, Nubia Rosa (Anais do Encontro de Teoria da Computação (ETC), 2020)
The development of solutions for the analysis of purchasing associations and consumer behavior is of great interest. One of the main challenges is to provide assertive results, with high accuracy, which enable the generation of strategic information to aid decision making. This paper presents an analysis of a supermarket sales data set by applying a hybrid solution based on data mining and complex networks. The results achieved reveal the potential of using complex networks in the information generation process.